Improved potency and reduced toxicity of the antifungal peptoid AEC5 through submonomer modification. Issue 22 (1st December 2018) - Middleton, Madyson P.; Armstrong, Scott A.; Bicker, Kevin L.
Graphical abstract: Highlights: An iterative SAR was carried out on the antifungal peptoid AEC5. Subtle modifications improved both antifungal potency and selectivity. β-5 shows promise to contribute to the challenging field of antifungals. Abstract: As proteolytically stable peptidomimetics, peptoids could serve as antifungal agents to supplement a therapeutic field wrought with toxicity issues. We report the improvement of an antifungal peptoid, AEC5, through an iterative structure-activity relationship study. A sarcosine scan was used to first identify the most pharmacophorically important peptoid building blocks of AEC5, followed by sequential optimization of each building block. The optimized antifungal peptoid from this study, β-5, has improved potency towards Cryptococcus neoformans and decreased toxicity towards mammalian cells. For example, the selectivity ratio for C. neoformans over mammalian fibroblasts was improved from 8 for AEC5 to 37 for β-5.